LES TUMEURS OSSEUSES PRIMITIVES DES MEMBRES AU CHU TOKOIN DE LOME PRIMARY BONE TUMORS OF MEMBERS IN TOKOIN TEACHING HOSPITAL OF LOME - Atchi, Walla; Yaovi, James Edem; Koami, Amakoutou; Anani, Abalo; Michel, Dossim Assang; Faré, Gnandi-Pio; Gamal, Ayouba (European Scientific Journal, ESJ, 2015)
Introduction. The purpose of this work was to analyze the epidemiological, diagnosis and therapy aspects of member’s primary bone tumors of our center to improve the management. Materials and Methods. We retrospectively analyzed the records of 32 patients treated for member’s primary bone tumors in orthopedic and trauma surgery department of Lomé Tokoin teaching hospital from January 1997 to December 2006. We collected and analyzed data on age, sex, clinical features, X-ray results, the results of the biopsy and therapeutic methods. Results. There were 13 men and 19 women. Pain was the most occasional discovery found in 84.38%. Swelling isolated or associated with pain was the second discovery circumstance in 75%. Pathological fracture showed the tumor in 12.5%. The tumor interested knee in 7 patients and leg in eight (8). Of the 21 patients (65,63%) diagnosed with benign tumors, there were 38.10% of osteogenic exostoses, 23.82% of osteoid osteoma and chondroma, the chondroblastoma, giant cell tumors then the aneurysmal cyst shared for each type 09, 52%. Osteosarcoma (5 patients; 45.46%), chondrosarcoma (3 patients; 27.27%) and Ewing’s sarcoma, fibrosarcoma then angiosarcoma (1 patient; 09.90% for each histological type) were the malignant bone tumors found. Benign tumors underwent conservative surgery. All 11 patients with malignant tumors were treated by amputation. Conclusion. The primary bone tumors are relatively rare member of the Tokoin teaching hospital of Lomé. Benign tumors are more frequent. The consultation delay does not facilitate the planning of their care. The malignant tumors are treated by member amputation. It is necessary to increase public awareness about the benefit of early consultation at the slightest symptoms suggestive and advocacy with governments to equip our center which is the national reference in adequate infrastructures and resources for tumors care especially primary bone malignancies.